Multi objective optimization using life cycle environmental impact and cost in the operation of utility plants - Martinez, Pablo Enrique (2009)
Environmental and economic objective functions are used simultaneously to select the operating conditions of a steam and power plant. Different methodologies to solve multi objective optimization problems were implemented successfully. The life cycle potential environmental impact and the operating cost of the power plant are minimized simultaneously. A methodology is presented to estimate the potential environmental impacts during the most important life cycle stages associated with imported fuel and electricity in the utility plant. Mixed Integer Non Linear multi objectives problems are formulated and different strategies are implemented and successfully solved in GAMS. © 2009 Elsevier B.V. All rights reserved.